2018
DOI: 10.1371/journal.ppat.1007269
|View full text |Cite
|
Sign up to set email alerts
|

SIVcol Nef counteracts SERINC5 by promoting its proteasomal degradation but does not efficiently enhance HIV-1 replication in human CD4+ T cells and lymphoid tissue

Abstract: SERINC5 is a host restriction factor that impairs infectivity of HIV-1 and other primate lentiviruses and is counteracted by the viral accessory protein Nef. However, the importance of SERINC5 antagonism for viral replication and cytopathicity remained unclear. Here, we show that the Nef protein of the highly divergent SIVcol lineage infecting mantled guerezas (Colobus guereza) is a potent antagonist of SERINC5, although it lacks the CD4, CD3 and CD28 down-modulation activities exerted by other primate lentivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 80 publications
(157 reference statements)
1
20
0
Order By: Relevance
“…However, these effects are also counteracted by HIV-1 Vpu and Env or require unphysiologically high levels of CD4 and are thus unlikely to account for the effect of Nef on HIV-1 spread in primary CD4 T cells (76)(77)(78). Moreover, two recent studies suggest that the ability of Nef to counteract the restriction to virion infectivity in a single round of infection by SERINC5 also does not translate into improved virus spread in these cells over multiple rounds of infection (75,79). As recently suggested for the MOLT3 T cell line, the Nef-mediated enhancement of HIV-1 spread in such cultures may thus reflect the antagonism of a yet-to-be-identified host cell restriction factor other than SERINC5, which may be counteracted by Nef via a S5AM-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, these effects are also counteracted by HIV-1 Vpu and Env or require unphysiologically high levels of CD4 and are thus unlikely to account for the effect of Nef on HIV-1 spread in primary CD4 T cells (76)(77)(78). Moreover, two recent studies suggest that the ability of Nef to counteract the restriction to virion infectivity in a single round of infection by SERINC5 also does not translate into improved virus spread in these cells over multiple rounds of infection (75,79). As recently suggested for the MOLT3 T cell line, the Nef-mediated enhancement of HIV-1 spread in such cultures may thus reflect the antagonism of a yet-to-be-identified host cell restriction factor other than SERINC5, which may be counteracted by Nef via a S5AM-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Nef genes were amplified by PCR with flanking primers introducing XbaI and MluI restriction sites for cloning into the bi-cistronic CMV promoter-based pCG IRES eGFP vector as described (54). pCG SMM tetherin and pBJ6 human SERINC5-HA protein expression vectors have been previously described (55,56).…”
Section: Expression Vectorsmentioning
confidence: 99%
“…To examine the expression of SIVsmm Nef proteins, HEK293T cells were transfected in 12-well dishes with 2.5 μg DNA of pCG IRES eGFP vectors expressing AU1-tagged Nefs. Two days post-transfection, cells were lysed and proteins separated, blotted and detected as previously described (56).…”
Section: Western Blotsmentioning
confidence: 99%
“…As with all primate lentiviruses, SIV has evolved to antagonize these factors. Studies have demonstrated that SIV Vpx and Vpr could degrade SAMHD1 [ 115 ], while Nef could antagonize tetherin [ 116 ] and SERINC5 [ 117 , 118 ]. Furthermore, it has been demonstrated that only SIV cpz and SIV smm Vif could effectively antagonize human APOBEC3G, highlighting one of the possible reasons why cross-species infection has been only observed with these two strains [ 119 ].…”
Section: Lentiviral Vector Systems Generated Based On Non-human Lementioning
confidence: 99%